Functional Characterization of Tea (Camellia sinensis) MYB4a Transcription Factor Using an Integrative Approach - Mingzhuo Li; Yanzhi Li; Lili Guo; Niandi Gong; Yongzheng Pang; Wenbo Jiang; Yajun Liu; Xiaolan Jiang; Lei Zhao; Yunsheng Wang; De-Yu Xie; De-Yu Xie; et al. (Frontiers in Plant Science, 2017)
Green tea (Camellia sinensis, Cs) abundantly produces a diverse array of phenylpropanoid compounds benefiting human health. To date, the regulation of the phenylpropanoid biosynthesis in tea remains to be investigated. Here, we report a cDNA isolated from leaf tissues, which encodes a R2R3-MYB transcription factor. Amino acid sequence alignment and phylogenetic analysis indicate that it is a member of the MYB4-subgroup and named as CsMYB4a. Transcriptional and metabolic analyses show that the expression profile of CsMYB4a is negatively correlated to the accumulation of six flavan-3-ols and other phenolic acids. GFP fusion analysis shows CsMYB4a’s localization in the nucleus. Promoters of five tea phenylpropanoid pathway genes are isolated and characterized to contain four types of AC-elements, which are targets of MYB4 members. Interaction of CsMYB4a and five promoters shows that CsMYB4a decreases all five promoters’ activity. To further characterize its function, CsMYB4a is overexpressed in tobacco plants. The resulting transgenic plants show dwarf, shrinking and yellowish leaf, and early senescence phenotypes. A further genome-wide transcriptomic analysis reveals that the expression levels of 20 tobacco genes involved in the shikimate and the phenylpropanoid pathways are significantly downregulated in transgenic tobacco plants. UPLC-MS and HPLC based metabolic profiling reveals significant reduction of total lignin content, rutin, chlorogenic acid, and phenylalanine in CsMYB4a transgenic tobacco plants. Promoter sequence analysis of the 20 tobacco genes characterizes four types of AC-elements. Further CsMYB4a-AC element and CsMYB4a-promoter interaction analyses indicate that the negative regulation of CsMYB4a on the shikimate and phenylpropanoid pathways in tobacco is via reducing promoter activity. Taken together, all data indicate that CsMYB4a negatively regulates the phenylpropanoid and shikimate pathways.Highlight: A tea (Camellia sinensis) MYB4a is characterized to encode a R2R3-MYB transcription factor. It is shown to repressively control the phenylpropanoid and shikimate pathway.